1998
DOI: 10.3171/jns.1998.88.4.0773
|View full text |Cite
|
Sign up to set email alerts
|

Unusual occipitoatlantal fracture dissociation with no neurological impairment

Abstract: The authors describe an unusual case of a complex traumatic fracture-dissociation injury of the craniovertebral junction, which the patient survived with no neurological damage. This case featured the rare combination of an avulsion of both the right occipital condyle and clivus and a fracture of the left lateral mass of the atlas. Because of the craniocervical ligament injury and the slight anterior occipitoatlantal dislocation, the lesion was considered to be unstable and was treated successfully with a cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
0
15
0
5
Order By: Relevance
“…Maughan et al [14] recently reported their patient treated by a new technique of occipito-C1 fixation rather than the typical surgical method of occipito-C2 or below fixation. Another re- ported occurrence of a rare combination of an avulsion of both the right occipital condyle and clivus and a fracture of the left lateral mass of the atlas was treated with a cervical collar [11]. In the present case, due to systemic problems, a rigid cervical collar was considered sufficient for cervical immobilization in a patient under sedation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Maughan et al [14] recently reported their patient treated by a new technique of occipito-C1 fixation rather than the typical surgical method of occipito-C2 or below fixation. Another re- ported occurrence of a rare combination of an avulsion of both the right occipital condyle and clivus and a fracture of the left lateral mass of the atlas was treated with a cervical collar [11]. In the present case, due to systemic problems, a rigid cervical collar was considered sufficient for cervical immobilization in a patient under sedation.…”
Section: Discussionmentioning
confidence: 93%
“…Routine use of multi-slice CT, resulted to an increase in the number of reported cases of occipital condyle fractures (OCFs) in the last decade [9,11,16]. Capuano et al [6] in a review of literature found 11 reported cases between 1817 and 1974 and 225 cases up to 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pode variar desde a parada cardiorrespiratória com quadriplegia a exame neurológico normal; algumas vezes, o paciente apresenta somente desconforto e rigidez cervical (16)(17) . A avaliação neurológica do paciente com lesão da coluna cervical alta é, muitas vezes, difícil, devido à presença de traumatismo craniencefálico associado; a origem do déficit neurológico pode permanecer indefinida na avaliação inicial (4,9,(18)(19) .…”
Section: Discussionunclassified
“…As a result of a maximum impact to the upper cervical spine one also has to expect further CSI associated with AOD. Thus, miscellaneous associated fractures C0-7, as well as discoligamentous instabilities have been reported in the case of AOD [13,14,17,22,29]. Small bony avulsions of the atlas, and also of the occipital condyles and odontoid tip are frequently seen in cases of AOD [3,30,31], whereas fractures of the occipital condyles endanger cranial nerves in their close neighborhood [2].…”
Section: Epidemiologymentioning
confidence: 99%